Molten FLiNaK salt infiltration into degassed nuclear graphite under inert gas pressure. (April 2015) - He, Zhoutong; Gao, Lina; Qi, Wei; Zhang, Baoliang; Wang, Xue; Song, Jinliang; He, Xiujie; Zhang, Can; Tang, Hui; Holmes, Rohan; Xia, Huihao; Zhou, Xingtai
Abstract: Infiltration of molten FLiNaK salt into degassed nuclear graphite samples under inert gas pressure was studied. The weight gain of different grades (2020, 2114, IG-110, NBG-8, G1 and G2) of nuclear graphite during infiltration with different pressures was measured. Molten salt infiltration was compared with mercury intrusion porosimetry where it was found that mercury infiltration was a useful predictor of the threshold pressure and infiltration volume per gram graphite for molten salt infiltration. The distribution and morphology of salt in the graphite were observed by scanning electron microscopy, with very little difference between the molten salt content at the center and edge of samples for samples infiltrated at pressure higher than the threshold pressure. Increased molten salt infiltration with increased pressure resulted from the occupation of smaller pores and full occupation of the larger irregular pores. The similarity of weight gain between molten salt infiltration equilibrated at 20 and 100 h showed 20 h was adequate to obtain equilibrium.